2022
DOI: 10.1192/bjo.2022.54
|View full text |Cite
|
Sign up to set email alerts
|

Crisis-focused psychosocial interventions for borderline personality disorder: systematic review and narrative synthesis

Abstract: Background Mental health crisis presentations are common in those who have a diagnosis of borderline personality disorder (BPD), and psychosocial interventions should be provided. However, there is limited evidence outlining what a crisis-focused psychosocial intervention for this population should include. Aims To conduct a systematic review and narrative synthesis of crisis-focused psychosocial interventions for people diagnosed with BPD. Method Three databases (MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The literature for acute care is smaller than for community care for people with this diagnosis, which is also under researched [ 67 ]. The review included studies that were found in the previous more focused reviews [ 10 , 12 ], but also included a wider range of literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature for acute care is smaller than for community care for people with this diagnosis, which is also under researched [ 67 ]. The review included studies that were found in the previous more focused reviews [ 10 , 12 ], but also included a wider range of literature.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review performed in 2022 of crisis interventions designed for people with a ‘personality disorder’ diagnosis found only two studies: a RCT of a brief admission intervention [ 9 ] and a pilot RCT of crisis planning [ 10 , 11 ], both reporting no effect of the study intervention compared to treatment as usual. A systematic review conducted in May 2022 searched for randomised and observational studies of crisis-focused psychosocial interventions for ‘borderline personality disorder’ that can be delivered within acute care and found five studies [ 12 ]. In four of these studies the intervention was a form of psychological therapy and in one study the intervention was joint crisis planning.…”
Section: Introductionmentioning
confidence: 99%
“…14 Unnecessary admissions may cause harm through psychological trauma and disconnection from ongoing psychotherapeutic approaches. 3 Repeated, frequent presentations to hospital can lead to negative outcomes including increased suicidality, through interference with out-patient treatment, workplace absences, reduction of self-agency, reinforcement of institutionalised dependency, and potentially, behavioural reinforcement of suicidality. 11,14 Hospital presentations may be correlated with BPD severity, or may be indicative of the relative insufficiency of existing services to coordinate care in meeting the complex needs of these patients.…”
Section: Crisis Access By Patients With Bpdmentioning
confidence: 99%
“…Patients with borderline personality disorder (BPD) who present repeatedly to Emergency Departments (EDs) with self-injury, intense affective lability and interpersonal dysfunction often receive unstructured, reactive, high-intensity and protracted inpatient care, aimed at providing immediate distress containment, despite the lack of evidence for its effectiveness. 1 , 2 , 3 Interpersonal dysfunction associated with BPD increases negative attitudes among clinicians. 4 Attitudes towards patients with BPD can be negative when compared to patients with other psychiatric diagnoses, partially related to a lack of education and training.…”
mentioning
confidence: 99%
“…9 There is presently insufficient data to recommend any specific psychosocial crisis intervention for people with BPD. 10…”
mentioning
confidence: 99%